2015
DOI: 10.1007/s10072-015-2100-x
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards physical activity in patients with multiple sclerosis: a cohort study

Abstract: Multiple sclerosis (MS) is a long-lasting neurological disease with onset in young adult age. Patients with MS are less active than healthy people, and their sedentary lifestyle might lead to secondary diseases or worsening of symptoms, disability and quality of life. In the study, we evaluated the attitude of physical activity (PA) of a group of MS patients and the differences in practice PA before and after the diagnosis. A randomly recruited group of patients with MS fulfilled a questionnaire about their at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…29,30 A recent study among 118 patients with MS found that, after diagnosis, 38% of participants stopped physical activity and many reduced frequency of activity. 31 In our study, participants could have possibly reduced physical activity in response to prediagnosis symptoms. 31 In an effort to address this, we carried out several analyses.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…29,30 A recent study among 118 patients with MS found that, after diagnosis, 38% of participants stopped physical activity and many reduced frequency of activity. 31 In our study, participants could have possibly reduced physical activity in response to prediagnosis symptoms. 31 In an effort to address this, we carried out several analyses.…”
Section: Resultsmentioning
confidence: 75%
“…31 In our study, participants could have possibly reduced physical activity in response to prediagnosis symptoms. 31 In an effort to address this, we carried out several analyses. Though total physical activity was weakly associated with a lower rate of MS in non-lagged analyses, this trend was no longer present when we carried out 6-year lagged analyses.…”
Section: Resultsmentioning
confidence: 75%
“…In summary, however, the items did not lie beyond the critical cut-off of .95, and, more importantly, there is a content-related argument for this finding. PwMS are typically well aware of the array of beneficial effects resulting from PA, especially when it is executed in a disease-adapted fashion (Frau et al, 2015). Therefore, we continued the development process with the inclusion of these two factors.…”
Section: Persons With Multiple Sclerosis (Study 1)mentioning
confidence: 99%
“…No language or date restrictions were applied. Bibliographic citations of relevant review articles 8,[29][30][31] were also searched to ascertain articles not identified through the database search.…”
Section: Search Strategymentioning
confidence: 99%